Assistance in Mining Reference Data for Writing Children's Reading on Climate Change: Pendampingan Penambangan Data Referensi Untuk Penulisan Bacaan Anak-Remaja Bertema Perubahan Iklim - Ari Ambarwati; Sunismi, Sunismi; Sri Wahyuni (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2024)
The impact of climate change has been felt by humans in various parts of the world. Mining reference data for writing stories for children and adolescents with the theme of climate change is a strategic point to be studied. The ability to write climate change-themed readings for children and adolescents requires adequate understanding of climate change issues. The purpose of the service is to improve the ability of members of the Saung Kanak community in Malang City to mine and manage reference data, as well as understand the issue of climate change, which has the potential to be used for children's and adolescent stories The service method is mentoring by carrying out a reference data mining workshop using Mendeley and Publish or Perish (PoP). The workshop was attended by 23 members of the Saung Kanak community in Malang City, followed by in-depth interviews, and circulated questionnaires to measure the achievement of the mentoring objectives. There was a positive correlation between participants' good understanding of the concept of data mining and the ability to mine data independently with a better level of understanding of climate change issues. Follow-up assistance that was specially formulated to reach 45.5% of 3 members of the Saung Kanak community in Malang City needs to be followed up, considering that they still have difficulty mining reference data.